Frequency of Gestational Diabetes among Women presenting with Premature Rupture of Membranes - Robeen, Kousar (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To evaluate the frequency of gestational diabetes among women who experience premature rupture of membranes Methodology: This descriptive cross-sectional study was conducted at the Department of Obstetrics & Gynecology, Mohammad Teaching Hospital Peshawar, from October 2021 to February 2022. One hundred fifty-five patients were selected from the Obstetrics and Gynaecology outpatient department. Women presenting with premature membrane rupture, within the reproductive age of 15-45 years, and with a gestational period beyond 37 weeks were included. Women with a history of failed inductions and those with twin pregnancies confirmed by ultrasound were excluded. A consecutive sampling of 155 females with premature rupture of membranes and screening them for gestational diabetes mellitus. The SPSS (version 22.0) was used for statistical analysis. Categorical variables, including gestational diabetes, parity, and gravidity, were summarized using frequencies and percentages. We conducted post-stratification analysis using the chi-square test, with a significance level set at p < 0.05. Results: The average age of the patients was 27.2±5.7 years, with the majority (49.7%) falling within the age range of up to 25 years. The mean parity was 2.49±1.84. Overall, we diagnosed gestational diabetes mellitus in 24.5% of the patients. Conclusion: The presence of gestational diabetes mellitus in cases of premature rupture of membranes is familiar in our population. We recommend conducting further studies to identify risk factors and develop preventive strategies before formulating recommendations for its prevention.